Traditional Chinese medicine strategies to optimize antibiotic use and reduce the burden of antibiotic resistance in Chinese children - Xue, Zhilong; Zheng, Yanzhi; Wei, Lina; Tian, Tong; Wu, Jiaqi; Jin, Aning; Sun, Liping (Frontiers in Public Health, 2024)
Antibiotic resistance is one of the greatest threats to human health, especially children's health. Traditional Chinese medicine encompasses several documented treatments for pediatric infectious diseases. The antibacterial efficacy and potential of traditional Chinese medicine to reverse bacterial resistance are gaining increasing research attention. This study explores the strategies that have been used to implement traditional Chinese medicine to optimize antibiotic use and reduce the burden of antibiotic resistance in children, as well as the challenges encountered. The findings emphasize the necessity for the Chinese government and the health community to take coordinated action, leveraging the unique strengths of traditional Chinese medicine to address the global health challenge posed by antibiotic resistance.